2008
DOI: 10.1159/000126925
|View full text |Cite
|
Sign up to set email alerts
|

Bone Mineral Density in End-Stage Renal Disease Patients: Association with Wasting, Cardiovascular Disease and Mortality

Abstract: Background: Bone and mineral disorders may contribute to extraosseous ossifications and cardiovascular disease (CVD) in end-stage renal disease (ESRD) patients. We have investigated the relationship between bone mineral density (BMD) and inflammation, wasting, CVD and mortality in ESRD patients. Methods: BMD (dual energy X-ray absorptiometry) and biochemical, nutritional and inflammatory markers were assessed in 277 incident ESRD patients (GFR 7.1 ± 0.2 ml/min) who were then followed prospectively for a mean o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 65 publications
2
26
0
1
Order By: Relevance
“…The association between decreased BMD and mortality has been described previously in non-dialysis and incident dialysis CKD populations [5,6,7]. Few studies have evaluated such relationship in maintenance hemodialysis patients.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The association between decreased BMD and mortality has been described previously in non-dialysis and incident dialysis CKD populations [5,6,7]. Few studies have evaluated such relationship in maintenance hemodialysis patients.…”
Section: Discussionmentioning
confidence: 94%
“…The association between arterial calcification and bone loss is believed to be one of the links that explain the relationship between decreased bone mass and poor cardiovascular outcomes. A handful of studies in non-dialysis and incident dialysis CKD populations reported the relationship between low BMD and cardiovascular disease (CVD) and mortality [5,6,7]. Such data in maintenance hemodialysis patients are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, recent clinical studies have shown that higher serum phosphate levels are strongly associated with vascular calcification and cardiovascular mortality among people who receive chronic dialysis [10][11][12][13][14][15] . Block et al [10] described, although in a post hoc analysis of a prospective trial, a direct relationship between hyperphosphatemia and mortality in dialysis patients.…”
Section: Introductionmentioning
confidence: 99%
“…Bone mineral metabolism is dysregulated in chronic kidney disease (CKD) patients starting from the early stages [3]. In extensive studies done on this population it is determined that dysregulated bone mineral metabolism is closely associated with increased risk of hi p fracture, cardiovascular disease and increased morbidity and mortality risk [4][5][6][7]. In end-stage renal disease (ESRD) patients, bone mineral densitometry was determined significantly lower than normal population and it is detected that in these patients as the duration of dialysis increases reduction of bone mineral density in densitometer becomes more evident [8].…”
Section: Introductionmentioning
confidence: 99%